Comparison of tooth crown discoloration with Epiphany and AH26 sealer in terms of chroma and value: an in vitro study - Fatemeh Shahrami; Mina Zaree; Arash Poorsattar Bejeh Mir; Mojtaba Abdollahi-Armani; Abbas Mesgarani (Universidade Estadual de Campinas, 2015)
Tooth crown discoloration may possess a heavy emotional burden and esthetic concern, especially when the anterior teeth are affected. Residue of sealers within the pulp chamber is a major contributor to the occurrence of tooth discoloration. Aim: The aim of this study was to evaluate the degree of crown discoloration when recently introduced sealer, Epiphany, is used. Methods: Forty human incisors were examined in vitro. Fifteen teeth were sealed with either AH26 or Epiphany sealer as experimental groups and root canals of the remaining 10 teeth with distilled water. Digital photographs of the buccal aspect of teeth were then examined in terms of brightness (value) and saturation (chroma) using Photoshop software at the beginning and consecutive 3, 6 and 9 months. Degree of brightness and saturation changes was defined as follows: less than 5% as slight, 10% to 15% as moderate and 15% to 20% as severe. Results: Fifteen, 14 and 10 teeth entered in Epiphany, AH26 and control groups, respectively. Significant brightness deterioration was noticed by time in both experimental groups [F (2, 8) =29.16, p<0.001], with no differences in Epiphany compared with AH26 (p=0.086). Saturation differed neither by time [F (2, 8) =0.129, p=0.881, nor by sealer type (p=0.136) during 9-month observation. At 9th month, crown segments (incisal, middle and cervical thirds) were not contrasted by the sealer type (p=0.982) or discoloration type (either brightness or saturation) (p=0.50). All changes in the experimental groups were significantly higher than the control group (p<0.001). Conclusions: Epiphany was equal to AH26 sealer in terms of relative long-term crown discoloration. One clinical correlation learned from the results of the present study is that Epiphany may safely be used interchangeably with the traditional AH26 sealer.